Uji Fitokimia dan Penapisan Senyawa Anti Malaria Asal Tumbuhan Benta (Wikstroemia sp.) terhadap Plasmodium falciparum - Helmi H. Helmi H.; Susanti I Susanti I; Fakhrurrozi Y Fakhrurrozi Y (Faculty of Mathtmatics and Natural Sciences, 2013)
Wikstroemia sp. is used in traditional medicine for medical purposes including malaria in Bangka and Belitung island. However, its use is largely based on the empirical experience rather than scientific investi-gation. The aim of this study is to identify the plant, to investigate the present of some kind of biochemical compound, and to evaluate in vitro antiplasmodial activity of ethanol extracts of Wikstroemia sp. leaves and fruits to Plasmodium falciparum. A visual method was allowed to evaluate the in vitro antiplasmodial activity of the extracts against P. falciparum. The number of parasites per 5,000 erythrocytes on thin Giemsa stained smears was calculated microscopically. IC50 values were determined by probit analysis of SPSS 13 program. The study showed, the plant was identified as Wikstroemia lanceolata. Some biochemical compound which have been investigated were phenol, saponin, and steroid. The antiplasmodial activity of ethanol extracts of Wikstroemia lanceolata fruits and leaves on P. falciparum were not effective as IC50>100 μg/mL. The highest inhibition of 100 μg/mL of Wikstroemia lanceolata fruits and leaves were 5.95% and 16.99% respectively.